Evaluation of Muscle Yield and Biochemical Properties of Several White Fleshed Fish from the Bay of Bengal for Nutraceutical Peptide Production (Journal of the Bangladesh Agricultural University, 2024)
Fish is recognized as an important functional food due to the presence of health promoting bioactive compounds. This study aimed to evaluate marine fish species with high muscle yield, low market value and year-round availability to be used as raw material in the production of nutraceutical compounds. A survey was conducted at Cox’s Bazar Sadar and Teknaf upazila in Cox’s Bazar district, Bangladesh targeting stakeholders involved in fish marketing and distribution through structured questionnaires. Nearly 100 fish species belonging to Ariidae, Sciaenidae, Leiognathidae, Nemipteridae, Trichiuridae, Carangidae, Scombridae, Clupeidae, Stromateidae, Mullidae, Harpadontidae, Synodontidae, Lutjanidae and Polynemidae landed at the artisanal landing centers. Of these, four croaker species were deemed suitable for muscle-derived fish peptide (FP) production. Accordingly, market-size Belanger’s croaker (Johnius belangerii), blackspotted croaker (Protonibeadia diacanthus), panna croaker (Panna microdon) and pawak croaker (Pennahia pawak) were collected and analyzed for muscle yield and proximate composition. White the muscle yield ranged from 20.7% to 35.2% of total weight with the highest yield observed in P. pawak which had high protein (18.43±0.3%) and low lipid (0.53±0.1%). A test FP powder prepared from P. microdon using 0.02% (w/w) commercial papain, yielding a product with 95.00±1.20% protein, 3.20±0.10% lipid, 1.30±0.10% moisture, 1.70±0.20% ash and 409.1±5.2 kcal energy per 100 g edible raw material that is comparable to high quality hydrolysates prepared from other fish and meat sources. The findings highlight the significant potential of marine fisheries resources to contribute to the global nutraceutical markets and create new economic opportunities for further exploration.J Bangladesh Agril Univ 22(4): 539-546, 2024